Hsa_circ_0002238 promotes the malignant behavior of colorectal cancer - Zhang, Lin-Ting; Zhou, Yuejia; Wang, Tiantian; Chen, Boran; Cai, Zhigao; Wang, Shubin; Tong, Gangling (Frontiers in Pharmacology, 2025)
BackgroundColorectal cancer (CRC) is one of the most common and deadly cancers worldwide. Circular RNAs (circRNAs) have emerged as crucial players in the onset and progression of CRC. This research aims to investigate the expression levels of a novel circRNA, hsa_circ_0002238, in CRC and to explore its association with alterations in CRC functional phenotypes.MethodsHigh-throughput RNA sequencing identified abnormal circRNA expressions, and qRT-PCR validated hsa_circ_0002238 expression. The relationship between hsa_circ_0002238 expression and the clinical data was analyzed by student’s t-test. Fluorescence in situ hybridization determined its cellular localization and expression in CRC cells. was conducted to ascertain the specific localization of hsa_circ_0002238 within cells and further confirm its expression in CRC cells. Following transfection with siRNA or plasmid, CRC cell proliferation was evaluated by CCK-8 assays and apoptosis was assessed by flow cytometry. We assessed changes in proliferation capacity among CRC cells exhibiting high levels of hsa_circ_0002238 using CCK-8 assays and flow cytometry analysis. Furthermore, flow cytometry was also used to evaluate apoptosis rates in these high-expressing CRC cells. In addition, wound healing and transwell assays were performed to assess changes in migratory and invasive capabilities associated with elevated hsa_circ_0002238 expression. The study additionally conducted in vivo experiments to validate the impact of hsa_circ_0002238 on the growth of CRC cells. Finally, Western blot was employed to analyze the expressions of epithelial-mesenchymal transition (EMT), serine/threonine kinase (AKT)/phosphatidylinositol 3 kinase (PI3K) signaling pathway, and apoptosis-related molecules.ResultsOur findings showed that hsa_circ_0002238 was significantly overexpressed in both CRC cell lines and tumor tissues. The expression level of hsa_circ_0002238 correlates with patient gender (p = 0.017) and shows significant diagnostic value (AUC = 0.765, 95%CI: 0.618–0.913, p = 0.004). At a relative expression level of 5.836, it achieves high sensitivity (50%) and specificity (100%). This upregulation promotes cellular proliferation, migration, invasion while inhibiting apoptosis within CRC cells. In vivo stuides, knockdown of hsa_circ_0002238 inhibited CRC tumor growth. Specifically, hsa_circ_0002238 facilitates EMT process characterized by markedly reduced E-cadherin levels alongside increased N-cadherin, vimentin and β-catenin expressions. Moreover, it induces elevated p-AKT and p-PI3K levels, increases cleaved caspase 3 and bcl-2, and decreases Bax expression in CRC cells, indicating that hsa_circ_0002238 enhances PI3K/AKT signaling and suppresses apoptosis. elevated p-AKT, levels along with cleaved caspase 3, bcl-2 expression within CRC, suggesting that hsa_circ_0002238 enhances AKT signaling and suppresses apoptosis.ConclusionOur research demonstrates that hsa_circ_0002238 expression significantly enhances CRC proliferation, migration, invasion, EMT process, PI3K/AKT signaling pathway while inhibiting apoptosis. Additionally, a preliminary association between hsa_circ_0002238 levels and patient gender was found, suggesting its potential as a diagnostic marker for CRC.